Wandering the In-Between, Where All Contradictions Concur. Confrontations with Anti-Indigenous Racism, White Colonial Pop Cultures, and Performance Traditions in the German-Speaking Context - Verena Melgarejo Weinandt; Suza Husse (The February Journal, 2025)
This article explores the role of performance as a colonial as well as anti-colonial cultural tool. It looks at how popular performance culture is used to create colonial imaginaries about Indigenous people in the German-speaking context, and how we can understand these imaginaries in connection to the realities and repetitions of colonial violence in the present. Based on their practice of working, thinking, and writing together as artists, researchers, and cultural workers, the two authors interlace biographically situated perspectives on the presence of anti-Indigenous racism and its rootedness in German society through colonial pop cultures and white performance traditions. The article is inspired by Melgarejo Weinandt’s performative alter ego Pocahunter engaged in a performance and multimedia practice countering colonial stereotyping and anti-Indigenous racism. Connecting to realities in the postsocialist East, where Husse grew up, cultural practices around ‘Indianthusiast’ spectacles, and museum cultures connected to the colonial writer Karl May, we think about ways to seek transformative modes of repair; in doing so, we look at different cultural expressions, artistic counter-practice, possible theoretical framings, modes of activism.